2020
DOI: 10.1109/access.2020.2995063
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsourcing Logistics Pricing Optimization Model Based on DBSCAN Clustering Algorithm

Abstract: From the perspective of platform economics, crowdsourcing is a very efficient business model, and the pricing of crowdsourcing tasks is a key factor for the sustainable development of the crowdsourcing model. In the logistics industry, crowdsourcing provides a new idea of sustainable development for logistics enterprises, and reasonable distribution pricing is the key to achieving sustainable development. This paper innovatively adds dynamic and decentralized characteristics of logistics on the basis of a deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…An improved DBSCAN algorithm is implemented at visible light communication systems to improve the signal-to-noise ratio and weaken the damage of noise to the communication quality [24]. A few more studies utilizing the DBSCAN algorithm in different fields of research can be found in very recent works [25][26][27][28]. On the other hand, importantly, the recent article [29] searches a way to determine the correct values of the DBSCAN parameters, by detecting the sharp increase in distance.…”
Section: Methodsmentioning
confidence: 99%
“…An improved DBSCAN algorithm is implemented at visible light communication systems to improve the signal-to-noise ratio and weaken the damage of noise to the communication quality [24]. A few more studies utilizing the DBSCAN algorithm in different fields of research can be found in very recent works [25][26][27][28]. On the other hand, importantly, the recent article [29] searches a way to determine the correct values of the DBSCAN parameters, by detecting the sharp increase in distance.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, employing regression methods, Li, Li [67] and Hao, Guo [65] examined the impacts of factors including workers' average distance from the given task point, distance between locations of tasks, workers' credit and reputation, workers' density within the given area, and tasks' density within the given area.…”
Section: Requester Pricingmentioning
confidence: 99%
“…e methods used in this pricing model mainly include cluster analysis, multiple regression, bivariate models, and Bayesian models. Literature [18] uses a density-based spatial clustering algorithm to cluster the density areas of the tasks in the task price dataset to optimize the pricing strategy. Literature [19] uses the same clustering method as literature [18] and introduces a proportional sharing mechanism to establish a sensing pricing optimization model that can evaluate task success rates in advance.…”
Section: Related Workmentioning
confidence: 99%